Embom (E-Module Batik Mangrove Organik) For Vocational High Schools - Veronika Yulisna Sinukaban; Lapisa , Remon; Maksum , Hasan; Rahmiati (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Schools still rely on textbooks in the batik learning process, so batik learning outcomes do not meet competency standards. Based on this, this research aims to produce a batik learning e-module that is valid, practical and effective. This type of research is development research. This research uses the four-D development model. The research subjects were 2 learning material experts, 2 learning media experts, and 3 teachers. The test subjects were 30 class XI students at SMK. The methods used to collect data are questionnaires and tests. Data collection instruments are questionnaires and questions. The data analysis technique used is descriptive. The research results show that the batik learning E-module produced is valid, practical, and effective in terms of appropriateness of the E-module content, E-module language, E-module presentation, and E-module graphics. The results of assessing the effectiveness of the mangrove organic batik E-module learning media in this research produced an N-Gain score of 0.71 so that the level of effectiveness was categorized as "High" with the interpretation "Effective". It was concluded that the Batik Learning E-module is suitable as an alternative reference material for developing the Batik E-module. The implication of this research is that the E-module developed can be used in learning.